TRAFFIC DISTRIBUTION STUDY ON MULTI-AIRPORT SYSTEMS IN THE GREATER JAKARTA METROPOLITAN AREA (GJMA) AND ASSOCIATED IMPLICATIONS - Faiz Agung Perdana; Richard Moxon (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2014)
Multi-airport system development is becoming a common solution to capacity constraint problems in metropolitan areas around the world. GJMA, as the biggest air transport market in Indonesia, have a plan to change their airport system from a single airport system to a multi-airport system because of capacity constraints. To relieve the congestion problem in the existing airport, an expansion project and a new airport plan are being proposed by the government. The new airport will be located in a green-field site around a hilly area in the Karawang Regency and plans to start operating in 2019.The government has not yet decided on the roles of the airport, but only proposed several scenarios to distribute the traffic for both airports. This study aims to understand the configuration of the traffic distribution of the new multi-airport system environment in GJMA, using a five step strategic planning methodology (CAIAD) which stands for Collect information, Analysing, Imaging, Assessing and Deciding.The results of the study show that the traffic distribution can lead to implications on the existing and planned infrastructure, and for the airport users. The main implications are traffic volatility, underutilized airport infrastructure, traffic demand, that cannot be accommodated by the airports, operational difficulty and poor service for the airport users. To minimize these implications, the government should start planning the development of the new airport based on flexibility related to the actual traffic demand and improved the transport access facilities. This study also suggests two scenarios as options for the government to implement in the GJMA multi-airport environment.Keywords: GJMA Airports, Capacity Constraint, Regulations Policy, Underutilize Airport and Airport Development.